In the wild - Elliott, David, 1947-; Meade, Holly (Somerville, Mass. : Candlewick Press, 2010)
A woodcut-illustrated collection of poems that celebrates wild animals.
Notable/Best Books (A.L.A.)
School Library Journal starred
Wilson's Children
Booklist, July 2010
Horn Book, September 2010
Kirkus Starred, July 2010
Keywords: Animals -- Juvenile poetry; Children's poetry, American; American poetry; Animals -- Poetry; American poetry; Animals -- Poetry; Picture books for children